Compression therapy in venous diseases: physical assumptions and clinical effects - Berszakiewicz, Andrzej; Sieroń, Aleksander; Krasiński, Zbigniew; Cholewka, Armand; Stanek, Agata (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2020)
Compression therapy (CT) is an established treatment method in chronic venous disease. Despite years of clinical experience, choosing the optimum compression therapy, including grade and pressure distribution, which determine the efficacy of treatment poses a challenge. The paper discusses CT physical assumptions (stiffness, elasticity, static and dynamic stiffness indices), clinical effects and contraindications to CT.